Turn Taking Patterns in Merisik Tradition of Malays Batubara Society - Prayogo Prayogo; Rozanna Mulyani; Eddy Setia (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
Merisik is a traditional ceremony that is in the Malay tribe. This event brought together two families, man and woman side. The purpose of this event is to know each other between the bride and groom. This event led by Bentara Sabda who had been appointed by each family. Thus, there are only two people who will interact in this event to represent each family. In this study,1) turn taking pattern,2) the relationship of utterances of the closest pair,3) the signs of the closest pair of utterances, and 4) how to obtain a turn of speech in Merisik, will be discussed. The method in this study is a descriptive qualitative. The results obtained are 1) having a perfect pattern that is in accordance with the ABAB formula, 2) there are two speech relationships and the closest pair of utterances, namely delivery and questions, 3) this event only obeys the two signs of the closest speech pair, namely utterances from different speakers and consists of two parts of speech, 4) there are two ways to get a turn of speech, namely by obtaining and seizing.